A Triple-Layered Comparative Approach to Understanding New Privacy Policy Practices of Digital Platforms and Users in China After Implementation of the PIPL - Liming Liu; Yiming Chen (Social Media + Society)
China enacted its first Personal Information Protection Law (PIPL) on 1 November 2021. However, there is a dearth of systematic research examining the implementation of new privacy policies exercised by digital platforms and user engagement with these policies. This study establishes a triple-layered comparative approach to explore the complexities and particularities of privacy policy practices in Chinese digital platforms. The methodology encompasses the analysis of privacy policies from representative platforms—WeChat, Taobao, and Douyin—alongside user experience garnered through a walkthrough method and insights from 28 interviews with platform users. Through critical discourse analysis, the research revealed that state-dominant policy discourses were ingrained in the formulation of platform privacy regulations to legitimize their authority over user data ownership. The users perceived a strong sense of passive protection, characterized by the rigid “agreement” discourse practices that underscore their vulnerability in everyday digital platform usage. The findings shed light on intricate power dynamics at play between platforms, their privacy policies, and users, which leads to polarized reactions from users toward privacy concerns. By examining the articulation of digital privacy policies as instruments of statecraft, we offer a nuanced view of describing non-Western experiences of privacy values and regulatory practices in the digital age.